Behaviour of stainless steel bolts after exposure to elevated temperatures. (June 2019) - Hu, Ying; Tang, Sheng-Lin; George, Adomako Kumi; Tao, Zhong; Wang, Xing-Qiang; Thai, Huu-Tai
Abstract: This paper presents experimental results of residual material properties of stainless steel bolts (austenitic grades A2–70 and A4–70) after exposure to elevated temperatures. Effects of temperature (20–900°C) and cooling method (cooling in air and cooling in water) on the mechanical properties (i.e., Young's modulus, yield stress, ultimate strength, ultimate strain and strain hardening exponent) of the two types of bolts are investigated. The residual properties of the stainless steel bolts are also compared with those of structural austenitic stainless steel and conventional high-strength structural bolts made of carbon steel. It was found that the exposure to elevated temperature only had a marginal influence on the residual behaviour of stainless steel bolts, which is consistent with the observation for structural austenitic stainless steel. In general, stainless steel bolts have superior post-fire performance compared with conventional carbon steel bolts. Based on the test data, an existing model proposed earlier for structural austenitic stainless steel was modified to predict stress-strain curves of stainless steel bolts after exposure to elevated temperatures. Highlights: The material properties of stainless steel bolts after exposure to elevated temperatures were studied in the experiments. The residual factor models of material properties after exposure to elevated temperatures were proposed. The constitutive model of stainless steel bolts was proposed for describing their material behavior after fire exposure. After exposure to elevated temperatures, the residual behavior of carbon steel bolts may not be as good as stainless bolts.